1998
DOI: 10.1046/j.1440-1711.1998.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Early pregnancy factor: An extracellular chaperonin 10 homologue

Abstract: Summary Early pregnancy factor (EPF) has been identi®ed as a homologue of chaperonin 10 (cpn10) with immunosuppressive and growth factor properties. As a homologue of cpn10, it belongs to the heat shock family of proteins (hsp) but, unlike other members of this family, EPF is detected extracellularly. Early pregnancy factor was ®rst discovered in pregnancy serum by the rosette inhibition test, and the novelty of its discovery was that its presence could diagnose pregnancy within 6±24 h of a fertile mating. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 118 publications
(140 reference statements)
3
34
1
5
Order By: Relevance
“…Anti-Hsp60 antibodies prevented and mimicked Hsp10 inhibitory activity, suggesting that Hsp10 may inhibit pro-inflammatory responses by interacting with extracellular Hsp60. We were unable to confirm earlier reports that Hsp10 has tumor growth factor properties (37)(38)(39)(40)(41). (42) (a kind gift from Prof. D. Hume, University of Queensland) were cultured (43) in the presence of G418 (200 g/ml) for 1 week after recovery from liquid nitrogen and grown as suspension cultures in 25-cm 3 flasks (Greiner Labortechnik, Frickenhausen, Germany).…”
contrasting
confidence: 88%
“…Anti-Hsp60 antibodies prevented and mimicked Hsp10 inhibitory activity, suggesting that Hsp10 may inhibit pro-inflammatory responses by interacting with extracellular Hsp60. We were unable to confirm earlier reports that Hsp10 has tumor growth factor properties (37)(38)(39)(40)(41). (42) (a kind gift from Prof. D. Hume, University of Queensland) were cultured (43) in the presence of G418 (200 g/ml) for 1 week after recovery from liquid nitrogen and grown as suspension cultures in 25-cm 3 flasks (Greiner Labortechnik, Frickenhausen, Germany).…”
contrasting
confidence: 88%
“…Since then, it was characterized to enter the serum and urine of pregnant women during the first and second trimesters (Morton et al 1977) and to be the principal immunosuppressive agent during pregnancy . Recently, EPF has been shown to be an extracellular homolog of the heat shock protein, Cpn10 (Summers et al 1996;Morton 1998). Further experiments have shown that Cpn10 is a potent stimulator of osteoclast recruitment and bone resorption (Summers et al 1996;Meghji et al 1997;Morton 1998).…”
Section: Many Faces Of Hsp10mentioning
confidence: 99%
“…It was present after 'few hours' in both women and several animal species. For a long time, it was difficult to reproduce the results outside the Australian continent, but early pregnancy factor is now a well-defined substance (Morton 1998, Schafer-Somi 2003. Modern molecular techniques open new pathways for the detection of an early pregnancy factor produced by the zygote in synergism with signal(s) amplified by cumulus and tubal cells (Hunter & Einer-Jensen 2003).…”
Section: Early Pregnancymentioning
confidence: 99%